Investigating neuroblastoma in childhood opsoclonus-myoclonus syndrome. Issue 5 (3rd April 2011) - Brunklaus, Andreas; Pohl, Keith; Zuberi, Sameer M; de Sousa, Carlos
Abstract : Objective: Opsoclonus-myoclonus syndrome (OMS) is a serious, often disabling neurological illness of early childhood which is frequently associated with occult neuroblastoma. As investigation methods vary significantly, the authors assessed the usefulness of imaging and metabolic studies in tumour detection. Methods: Retrospective case note review of 101 OMS patients from two paediatric neurology centres over 53 years. Results: The prevalence of neuroblastoma in OMS was 8% in the 1970s, 16% in the 1980s, 38% in the 1990s and 43% in the 2000s, with tumours being mainly low grade. CT/MR imaging of the chest and abdomen was the most accurate test to detect occult neuroblastoma. Poorer sensitivities were noted for metaiodobenzylguanidine scintigraphy and urine catecholamines, reflecting the low metabolic activity of these tumours. Conclusion: CT/MR imaging has the highest detection rate of neuroblastoma and this should be reflected in investigation protocols to achieve the best possible outcome for children with OMS.